2018
DOI: 10.1089/lrb.2016.0048
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Stiffness in Postmastectomy Lymphedema Using Acoustic Radiation Force Impulse Imaging: A Prospective Randomized Controlled Study for Identifying the Optimal Pneumatic Compression Pressure to Reduce Stiffness

Abstract: IPC can reduce stiffness and subcutaneous tissue thickness of the proximal upper arm in patients with PMLE. A pressure of 35 mmHg yields the largest improvement of stiffness; higher compression pressure did not yield any additional improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…Hayashi et al reported a moderate positive correlation between strain elastography and indocyanine green lymphography, which is used for diagnosing lymphatic obstructions. The data on the use of SWE for the diagnosis of lymphedema are limited . Chan et al found the SWV of the cutaneous and subcutaneous tissue of limbs with lymphatic obstruction to be significantly greater than that of unaffected limbs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Hayashi et al reported a moderate positive correlation between strain elastography and indocyanine green lymphography, which is used for diagnosing lymphatic obstructions. The data on the use of SWE for the diagnosis of lymphedema are limited . Chan et al found the SWV of the cutaneous and subcutaneous tissue of limbs with lymphatic obstruction to be significantly greater than that of unaffected limbs.…”
Section: Discussionmentioning
confidence: 99%
“…The swelling in lymphedema is caused by excess extracellular water, filtered plasma cells, and stromal cell products that induce adipose tissue hypertrophy and the deposit of excess extracellular matrix substances. In the chronic stage, this deposit causes fibrosis, repeated infections, poor skin cosmesis, psychological issues, and, occasionally, the development of lethal lymphangiosarcoma . Therefore, preventive strategies and the early detection and treatment of lymphedema are important for preventing the progression to the advanced fibrotic stages and related morbidities.…”
mentioning
confidence: 99%
See 3 more Smart Citations